Beyond the anima: approximations between object theater and performance art (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
This article reflects on the action of animating as a structuring element in puppet theater and its overcoming brought about by some trends in object theater, a strand of contemporary animation theater that uses everyday artifacts instead of puppets in its assemblies. It is argued that, while they intentionally distance themselves from animation and its associated techiniques, these artists and groups start to value other procedures similar to those in the field of performance art. It is concluded that such movement contributes to broadening the horizon of possibilities in the theater of objects.
Keywords: theater; animation; puppet; object; performance